Tagging and Shallow Processing of Portuguese: Workshop Notes of TASHA'2003 - Branco, António Horta (2009)
Recent advances on tagging and other shallow processing tools have confirmed the key importance of these applications to enable subsequent stages of efficient deep linguistic processing, and to improve the quality of information retrieval services and support the semantic web. These tools include tokenizers, stemmers, MWU detectors, POS taggers, named entity recognizers, NP chunkers, WSD tools, PP attachment resolvers, terminology extractors, etc. Their development involve a wide variety of problems and resources, ranging from the collection of stop lists to the integration of these tools into broader systems and applications, and including a.o. methodologies for accurate hand tagging, linguistic resources for training and evaluation, learning algorithms and their eventual tuning to Portuguese, finite-state solutions, evaluation metrics and results, selected linguistic generalizations and specifications, etc. The Workshop on Tagging and Shallow Processing of Portuguese (TASHA'2003) took place at the University of Lisbon, October 3, 2003. Its goal was to provide a forum to discuss experiences and exchange results between researchers working in this area, and to review the current state of the art in this diverse field in what concerns the Portuguese language. The present collection of notes includes the abstracts of papers selected to be presented at the workshop. These abstracts are extended versions of the anonymous abstracts originally submitted and take into account the remarks offered by the reviewers, to the extent that this was possible by the space constraints of the present publication